2019
DOI: 10.1177/0269881118817387
|View full text |Cite
|
Sign up to set email alerts
|

Risk of readmission in patients with schizophrenia and schizoaffective disorder newly prescribed clozapine

Abstract: Background:Insight into the effect of clozapine is limited by a lack of controlling for confounding variables in current research. Our objective was to investigate the association between clozapine prescribed at discharge, following an inpatient episode, and risk of readmission into secondary mental health services in patients with schizophrenia and schizoaffective disorder, controlling extensively for confounding variables.Methods:Clinical records from 3651 patients were analysed in a retrospective observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Pharmaco-epidemiological studies have consistently shown that clozapine treatment is associated with a reduction in all-cause mortality (Cho et al, 2019a; Wimberley et al, 2017), and this seems to be driven by a reduction in suicidality (Meltzer and Okayli, 1995; Meltzer et al, 2003; Wimberley et al, 2017). Clozapine has been shown to reduce admission rates compared with other antipsychotics (Kesserwani et al, 2019) and in within-patient mirror-image studies (Siskind et al, 2019), and a recent meta-analysis showed lower admission rates under clozapine than any other drug, including LAIs (Land et al, 2017). Clozapine treatment is also associated with lower rates of treatment failure than any other oral antipsychotics (Tiihonen et al, 2017).…”
Section: Treatment-resistant Schizophreniamentioning
confidence: 99%
“…Pharmaco-epidemiological studies have consistently shown that clozapine treatment is associated with a reduction in all-cause mortality (Cho et al, 2019a; Wimberley et al, 2017), and this seems to be driven by a reduction in suicidality (Meltzer and Okayli, 1995; Meltzer et al, 2003; Wimberley et al, 2017). Clozapine has been shown to reduce admission rates compared with other antipsychotics (Kesserwani et al, 2019) and in within-patient mirror-image studies (Siskind et al, 2019), and a recent meta-analysis showed lower admission rates under clozapine than any other drug, including LAIs (Land et al, 2017). Clozapine treatment is also associated with lower rates of treatment failure than any other oral antipsychotics (Tiihonen et al, 2017).…”
Section: Treatment-resistant Schizophreniamentioning
confidence: 99%
“…35 Other research conducted in the UK found that patients with schizophrenia or schizoaffective disorder who have been newly prescribed with clozapine have a decreased risk of readmission, even if these patients had more severe psychopathology and poorer functional status. 36 A systematic review on the impact of clozapine on hospital use also found that clozapine reduced the proportion of people admitted to hospital compared with controls. 37 The authors hypothesised that the reason for this protective effect may be because of the need for ongoing regular haematological monitoring, where deteriorations in mental state may be detected earlier.…”
Section: Main Findingsmentioning
confidence: 99%
“…2 Clozapine has been shown in several pharmacoepidemiological studies to show superior long-term efficacy in terms of reducing hospital admissions. 3 It also surpasses other antipsychotics in reducing self-harm 4 and overall mortality. 5 The pharmacological basis for the unique efficacy of clozapine in treatment-resistant schizophrenia is not clearly understood.…”
mentioning
confidence: 99%